High-performance silicon carbide ceramic composite material and method for preparing the same
Patent Information
- Application Number
- CN202611230161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-20
AI Technical Summary
然而,该类工艺流程复杂,且裂解过程中仍容易产生孔隙和结构缺陷,影响最终陶瓷性能
本发明以SiC粉体和未经预交联及预热解处理的碳化钛前驱体为原料,经分散混合与蒸发干燥后得到复合粉体;随后将复合粉体进行老化处理,并采用放电等离子烧结进行致密化制备,得到高性能SiC复合陶瓷。烧结过程中,碳化钛前驱体原位裂解形成纳米TiC相和石墨化碳相,所述裂解产物分布于SiC晶界处,其中纳米TiC相能够细化晶粒并提高材料强度,石墨化碳相能够促进裂纹偏转和裂纹扩展耗能,提高材料断裂韧性。本发明无需添加传统氧化物烧结助剂,即可在较低烧结温度下获得高致密度、高硬度、高强度和高韧性的SiC复合陶瓷,其相对密度可达到97%以上。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to a high-performance silicon carbide ceramic composite material and its preparation method, belonging to the field of ceramic materials technology. Background Technology
[0002] Silicon carbide (SiC) ceramics possess high hardness, high wear resistance, high thermal conductivity, corrosion resistance, and excellent high-temperature stability, making them promising for applications in protection, aerospace, nuclear energy, and high-temperature structures. However, due to the strong covalent bonds and low self-diffusion coefficient of SiC, its densification through sintering is difficult, typically requiring temperatures above 2000℃ or high pressure conditions, resulting in high manufacturing costs. Currently, oxide sintering aids such as Al2O3 and Y2O3 are commonly used to promote SiC densification, but these oxide aids tend to form glassy phases or second phases at grain boundaries, thereby reducing the material's high-temperature performance, hardness, and wear resistance.
[0003] Polymer-derived ceramics (PDCs) technology offers a new approach for the low-temperature preparation of ceramic materials. Existing PDC technologies typically require pre-crosslinking, curing, or pre-pyrolysis of the precursor to avoid closed-pore defects caused by the release of large amounts of gas during sintering. However, such processes are complex, and pyrolysis can still easily generate porosity and structural defects, affecting the final ceramic properties.
[0004] Furthermore, the inherent brittleness and low fracture toughness of SiC ceramics limit their further applications. Therefore, there is an urgent need to develop a method for preparing SiC composite ceramics that requires no sintering aids or pre-crosslinking treatment, enables rapid densification at low temperatures, and combines high strength with high toughness. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a high-performance silicon carbide ceramic composite material and its preparation method. The inventors discovered that directly mixing SiC powder and an organotitanium polymer precursor to form a slurry, followed by aging and spark plasma sintering, can improve sintering uniformity and promote low-temperature densification under the synergistic effect of aging and vacuum degassing. Specifically, the uncrosslinked titanium carbide precursor possesses good fluidity and interfacial wetting ability, and during aging, it can further migrate, spread, and adsorb onto the surface of SiC particles, thereby forming a uniform coating structure. Subsequently, a vacuum holding stage is set in the early stage of spark plasma sintering to fully expel the small molecule gases generated by precursor decomposition. Finally, a staged heating and pressurizing sintering regime matching the precursor decomposition behavior is adopted to avoid the retention of volatile gases due to premature pressurization during decomposition, while also ensuring rapid densification in the later stages.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows.
[0007] A method for preparing a high-performance silicon carbide ceramic composite material, comprising the following steps: (1) Preparation of composite powder: SiC powder and titanium carbide precursor are added to an organic solvent and dispersed evenly to obtain a mixed slurry; then the mixed slurry is evaporated and dried to obtain composite powder; wherein, the titanium carbide precursor is an organic titanium polymer precursor that can form TiC phase after pyrolysis, and the elements contained include Ti, C, O and H elements; with the total mass of SiC powder and titanium carbide precursor as 100%, the amount of titanium carbide precursor added is 2.5wt.%~7.5wt.%; (2) Aging treatment: The composite powder is sealed and placed for more than 72 hours to obtain the aged composite powder; (3) Spark plasma sintering: The aged composite powder is placed in a spark plasma sintering equipment for sintering: First stage: vacuum to below 20 Pa, heat to 850±50℃ and hold, and continue heating after the vacuum in the furnace chamber returns to below 20 Pa; Second stage: heat to 1350±50℃ and start pressurizing, and when the temperature rises to 1600±20℃, the sintering pressure increases to 50±10MPa; Third stage: keep the pressure constant, continue heating to 1640~1750℃, hold for 2~10 min, and cool with the furnace after sintering to obtain a high-performance silicon carbide ceramic composite material; wherein, the heating rate of the three stages decreases in a gradient; the ceramic composite material includes a SiC matrix and nano-TiC phase and graphitized carbon phase distributed at the grain boundaries.
[0008] Preferably, in step (1), the titanium carbide precursor, based on the total mass of Ti, C, O, and H elements as 100%, has a Ti element content ≥15 wt.%, a C element content ≥53 wt.%, a H element content ≤7 wt.%, an O element content ≤25 wt.%, a ceramicization yield at 1200℃ ≥20 wt.%, and a viscosity ≤200 mPa·s. More preferably, the titanium carbide precursor has a Ti element content of 15~20 wt.%, a C element content of 53~60 wt.%, an O element content of 15~25 wt.%, and the balance being H elements.
[0009] Preferably, in step (1), the amount of titanium carbide precursor added is 4wt.%~6wt.%.
[0010] Preferably, in step (1), the titanium carbide precursor is polytitanium carbide.
[0011] Preferably, in step (1), the SiC powder is granulated powder with a particle size of 40~60 micrometers.
[0012] Preferably, in step (1), the organic solvent is ethanol or xylene.
[0013] Preferably, in step (1), the drying is carried out by rotary evaporation, and the evaporation temperature is 50~80℃.
[0014] Preferably, in step (2), the composite powder is sealed and placed for 72-120 hours. The inventors have found that during the aging process, the precursor can further infiltrate, migrate, and adsorb onto the surface of SiC particles, thereby improving the uniformity of the precursor coating and enhancing subsequent sintering stability. When the aging time is less than 48 hours, the precursor distribution is uneven, and local closed pores are easily formed during sintering; when the aging time reaches 72 hours or more, the sintering uniformity and densification of the composite powder can be significantly improved.
[0015] Preferably, in step (3), the heating rate in the first stage is 90~110℃ / min.
[0016] Preferably, in step (3), the heating rate in the second stage is 40~60℃ / min.
[0017] Preferably, in step (3), the heating rate in the second stage is 20~30℃ / min.
[0018] A high-performance silicon carbide ceramic composite material was prepared by the above method.
[0019] Preferably, the relative density of the ceramic composite material is ≥97%.
[0020] Preferably, the ceramic composite material has a hardness of 25~30 GPa, a flexural strength of 470~650 MPa, and a fracture toughness of 7~10 MPa·m. 1 / 2 .
[0021] Beneficial effects This invention uses SiC powder and uncrosslinked and unpyrolyzed titanium carbide precursors as raw materials. After dispersion, mixing, and evaporation drying, a composite powder is obtained. Subsequently, the composite powder undergoes aging treatment and densification is achieved through spark plasma sintering to obtain high-performance SiC composite ceramics. During sintering, the titanium carbide precursor undergoes in-situ pyrolysis to form nano-TiC phase and graphitized carbon phase. The pyrolysis products are distributed at the SiC grain boundaries. The nano-TiC phase refines the grains and improves the material strength, while the graphitized carbon phase promotes crack deflection and crack propagation energy dissipation, improving the material's fracture toughness. This invention achieves high density, high hardness, high strength, and high toughness SiC composite ceramics at relatively low sintering temperatures without the need for traditional oxide sintering aids, with a relative density exceeding 97%.
[0022] (1) The present invention uses uncrosslinked titanium carbide precursors to directly participate in sintering, eliminating the need for pre-crosslinking and pre-pyrolysis steps in the traditional PDC process, which significantly simplifies the process and reduces the preparation cost.
[0023] (2) The redistribution and interfacial adsorption of precursors on the surface of SiC particles induced by aging improve the uniformity and sintering stability of composite powder.
[0024] (3) By setting a low-temperature holding stage in the early stage of sintering and maintaining a low vacuum environment in the furnace cavity, the volatile gases generated during the precursor pyrolysis process are fully discharged, reducing the probability of closed pores and microcracks and improving sintering stability. Then, when the powder enters the obvious shrinkage stage at 1350±50℃, the sintering pressure is applied, and the pressure is completed during the process of heating to 1600±20℃. This allows the precursor pyrolysis, particle rearrangement, sintering neck formation, and diffusion densification processes to match each other, avoiding the retention of pyrolysis gases while promoting the rapid elimination of pores, and achieving rapid densification of SiC composite ceramics at a lower sintering temperature. This staged heating and pressurizing sintering system, which matches the pyrolysis behavior of the precursor, avoids the retention of volatile gases due to premature pressure during the pyrolysis process, while taking into account the rapid densification in the later stage, and achieves coordinated control of the precursor pyrolysis, gas discharge, and sintering densification processes.
[0025] (4) The nano-TiC phase formed in situ during sintering can refine the grains and improve the strength of the material.
[0026] (5) The graphitized carbon phase formed in situ can promote crack deflection and bridging, and improve the fracture toughness of the material.
[0027] (6) The present invention can obtain SiC composite ceramics with high density, high strength and high toughness at a lower sintering temperature without the introduction of traditional oxide sintering aids. Attached Figure Description
[0028] Figure 1 The Fourier transform infrared spectrum and TG curve of the titanium carbide precursor are shown.
[0029] Figure 2 The images show the SEM and XRD patterns of the SiC composite ceramics prepared in Example 1.
[0030] Figure 3 The images shown are SEM, XRD, Raman, TEM, and EDS images of the SiC composite ceramics prepared in Example 2.
[0031] Figure 4 The images shown are SEM and XRD patterns of the SiC composite ceramics prepared in Example 3.
[0032] Figure 5The image shows a SEM image of the SiC ceramic prepared in Comparative Example 1. Detailed Implementation
[0033] The present invention will be further described in detail below with reference to specific embodiments.
[0034] Example 1 Step (1) Raw material preparation: Weigh 9.75 g of SiC powder (40~60 micrometer granulated powder) and 0.25 g of titanium carbide precursor.
[0035] The titanium carbide precursor was not crosslinked or pre-ceramicized. The inventors found that the uncrosslinked precursor has better fluidity and interfacial wetting ability, and can form a more uniform coating structure on the surface of SiC particles. However, after crosslinking or pre-pyrolysis treatment, the fluidity of the precursor decreases, making it difficult to distribute it uniformly on the surface of SiC particles through solid-liquid coating. It usually needs to be mechanically mixed by ball milling, and the mixing uniformity is lower than that of the aforementioned solid-liquid coating method.
[0036] The titanium carbide precursor used in this embodiment was purchased from Forsmann Technology (Beijing) Co., Ltd. The titanium carbide precursor resin (ceramization yield ≥22%, viscosity ≤200 mPa·s) is an organotitanium polymer precursor capable of forming a TiC phase after pyrolysis. The Fourier transform infrared spectrum and TG curve of the precursor are shown below. Figure 1 As shown. In the titanium carbide precursor, the Ti content is 15.29 wt.%, the C content is 53.30 wt.%, the H content is 6.27 wt.%, the O content is 25.14 wt.%, and the ceramization yield at 1200℃ is 25 wt.%.
[0037] Step (2) Preparation of composite powder: SiC powder and titanium carbide precursor were added to a solvent and magnetically stirred at 800 r / min for 3 h to obtain a uniform slurry. Then, the slurry was dried under negative pressure by rotary evaporation at a temperature of 70 °C, a flask rotation speed of 30 r / min, and a drying time of 1 h to obtain the dried composite powder.
[0038] Step (3) Aging treatment: The obtained composite powder is sealed and placed for 72 hours.
[0039] Step (4) Spark Plasma Sintering: The composite powder is loaded into a graphite mold and placed in a spark plasma sintering apparatus. First, the vacuum is evacuated to below 20 Pa; then the temperature is increased to 800 °C at 100 °C / min and held until the volatile gases generated by the precursor decomposition are fully discharged and the vacuum in the furnace chamber returns to below 20 Pa, then the temperature is increased again; the temperature is increased to 1350 °C at 100 °C / min and pressure is applied; the temperature is increased to 1600 °C at a rate of 50 °C / min and the pressure is increased to 60 MPa; the pressure is kept constant and the temperature is increased to 1700 °C at 30 °C / min and held for 5 min; after sintering, the furnace is cooled to obtain SiC composite ceramic.
[0040] The SEM and XRD test results of the SiC composite ceramic are as follows: Figure 2 As shown. Testing revealed that the composite ceramic comprises a SiC matrix and nano-TiC and graphitized carbon phases distributed at the grain boundaries. The obtained sample has a relative density of 98.8%, a hardness of 26 GPa, a flexural strength of 490 MPa, and a fracture toughness of 7.0 MPa·m. 1 / 2 .
[0041] Example 2 In step (1), 9.5g of SiC powder (granulated powder with a particle size of 40-60 micrometers) and 0.5g of titanium carbide precursor were used, and the remaining steps were the same as in Example 1. The resulting sample had a relative density of 98.7%, a hardness of 26 GPa, a flexural strength of 604 MPa, and a fracture toughness of 8.0 MPa·m. 1 / 2 .
[0042] from Figure 3 As can be seen from the Raman spectrum, the intensity of the G peak is significantly higher than that of the D peak, indicating that the carbon phase formed by pyrolysis has a high degree of ordering. Simultaneously, high-resolution TEM results show the presence of regular layered lattice fringes, further confirming the formation of a graphitized carbon structure. Furthermore, EDS results show significant Ti enrichment in localized areas; combined with XRD and TEM analysis results, this indicates that the region corresponds to a nano-TiC phase. The composite ceramic comprises a SiC matrix and nano-TiC and graphitized carbon phases distributed at the grain boundaries.
[0043] Example 3 In step (1), 9.25g of SiC powder (granulated powder with a particle size of 40-60 micrometers) and 0.75g of titanium carbide precursor were used, and the remaining steps were the same as in Example 1. The resulting sample had a relative density of 98.7%, a hardness of 26 GPa, a flexural strength of 471 MPa, and a fracture toughness of 7.7 MPa·m. 1 / 2 The SEM and XRD test results of the SiC composite ceramic are as follows: Figure 4As shown. Tests have shown that the composite ceramic comprises a SiC matrix and nano-TiC and graphitized carbon phases distributed at the grain boundaries.
[0044] Comparative Example 1 10 grams of SiC powder (40-60 micrometer granulated powder) was weighed and placed into a graphite mold, and then placed in a spark plasma sintering apparatus. First, a vacuum was drawn to below 20 Pa; then the temperature was increased to 800 °C at 100 °C / min and held until the vacuum in the furnace chamber returned to below 20 Pa, and the temperature was increased again; the temperature was increased to 1350 °C at 100 °C / min and pressure was applied; when the temperature reached 1600 °C, the pressure was increased to 60 MPa; the pressure was kept constant, and the temperature was increased to 1700 °C at 30 °C / min and held for 5 min; after sintering, the furnace was cooled to obtain SiC ceramic.
[0045] The resulting sample had a relative density of less than 80%. Figure 5 As can be seen, the fracture surface contains a large number of pores, which is much higher than that of the sample with added titanium carbide precursor. This indicates that the powder without added titanium carbide precursor has poor sintering properties.
[0046] Comparative Example 2 In step (1), 9.0 g of SiC powder (40-60 micrometer granulated powder) and 1.0 g of titanium carbide precursor were used, and the remaining steps were the same as in Example 1. The relative density of the obtained sample was less than 85%. The results show that when the amount of titanium carbide precursor added is too high, the large amount of gas generated by cracking will deteriorate the sintering densification behavior and reduce the material properties.
[0047] Comparative Example 3 Steps (1) and (2) are the same as in Example 1, but the aging step is omitted. The relative density of the obtained sample is less than 95%. The results show that the composite powder without aging treatment has poor sintering stability and is prone to forming pore defects.
[0048] In summary, this invention achieves rapid densification of SiC ceramics at low temperatures through the synergistic regulation of uncrosslinked precursors, aging-induced interface reconstruction, and pyrolysis exhaust, resulting in excellent comprehensive mechanical properties.
[0049] In summary, the invention includes, but is not limited to, the above embodiments. Any equivalent substitutions or partial improvements made under the spirit and principles of this invention shall be considered to be within the protection scope of this invention.
Claims
1. A method for preparing a high-performance silicon carbide ceramic composite material, characterized in that: The method steps include: (1) Preparation of composite powder: SiC powder and titanium carbide precursor are added to an organic solvent and dispersed evenly to obtain a mixed slurry; then the mixed slurry is evaporated and dried to obtain composite powder; wherein, the titanium carbide precursor is an organic titanium polymer precursor that can form TiC phase after pyrolysis, and the elements contained include Ti, C, O and H elements; with the total mass of SiC powder and titanium carbide precursor as 100%, the amount of titanium carbide precursor added is 2.5wt.%~7.5wt.%; (2) Aging treatment: The composite powder is sealed and placed for more than 72 hours to obtain the aged composite powder; (3) Spark plasma sintering: The aged composite powder is placed in a spark plasma sintering equipment for sintering: First stage: vacuum to below 20 Pa, heat to 850±50℃ and hold, and continue heating after the vacuum in the furnace chamber returns to below 20 Pa; Second stage: heat to 1350±50℃ and start pressurizing, and when the temperature rises to 1600±20℃, the sintering pressure increases to 50±10MPa; Third stage: keep the pressure constant, continue heating to 1640~1750℃, hold for 2~10 min, and cool with the furnace after sintering to obtain a high-performance silicon carbide ceramic composite material; wherein, the heating rate of the three stages decreases in a gradient; the ceramic composite material includes a SiC matrix and nano-TiC phase and graphitized carbon phase distributed at the grain boundaries.
2. The method for preparing a high-performance silicon carbide ceramic composite material as described in claim 1, characterized in that: In step (1), the titanium carbide precursor, based on the total mass of Ti, C, O, and H elements as 100%, has the following composition: Ti element content ≥ 15 wt.%, C element content ≥ 53 wt.%, H element content ≤ 7 wt.%, O element content ≤ 25 wt.%, ceramization yield at 1200℃ ≥ 20 wt.%, and viscosity ≤ 200 mPa·s; preferably, the titanium carbide precursor has a Ti element content of 15~20 wt.%, a C element content of 53~60 wt.%, an O element content of 15~25 wt.%, and the balance being H element.
3. The method for preparing a high-performance silicon carbide ceramic composite material as described in claim 1, characterized in that: In step (1), the amount of titanium carbide precursor added is 4wt.%~6wt.%.
4. The method for preparing a high-performance silicon carbide ceramic composite material as described in claim 1, characterized in that: In step (1), the titanium carbide precursor is polytitanium carbide silane; the SiC powder is granulated powder with a particle size of 40~60 micrometers.
5. The method for preparing a high-performance silicon carbide ceramic composite material as described in claim 1, characterized in that: In step (1), the organic solvent is ethanol or xylene; Drying is carried out by rotary evaporation at a temperature of 50-80℃.
6. The method for preparing a high-performance silicon carbide ceramic composite material as described in claim 1, characterized in that: In step (2), the composite powder is sealed and placed for 72~120h.
7. The method for preparing a high-performance silicon carbide ceramic composite material as described in claim 1, characterized in that: In step (3), the heating rate in the first stage is 90~110℃ / min; the heating rate in the second stage is 40~60℃ / min; and the heating rate in the third stage is 20~30℃ / min.
8. A high-performance silicon carbide ceramic composite material, characterized in that: It is prepared by the method described in any one of claims 1 to 7.
9. The high-performance silicon carbide ceramic composite material as described in claim 8, characterized in that: The relative density of the ceramic composite material is ≥97%.
10. The high-performance silicon carbide ceramic composite material as described in claim 8, characterized in that: The ceramic composite material has a hardness of 25~30 GPa, a flexural strength of 470~650 MPa, and a fracture toughness of 7~10 MPa·m. 1 / 2 .